2022
DOI: 10.1002/hed.27136
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of head and neck lymphedema assessment

Abstract: Head and neck lymphedema (HNL) is an increasingly recognized complication of head and neck cancer and its treatment. However, no consensus exists on the "gold-standard" assessment tool for the purposes of diagnosis, classification, or monitoring of HNL. We conducted a systematic review of the literature regarding HNL assessment to determine the optimal method/s of assessment for patients with HNL. A review of publications between January 2000 and September 2021 was undertaken on four electronic databases. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…This is just over half of the historically reported low range of 12% and a small fraction of the incidence of 90% reported in contemporary studies. [8][9][10][11][12] Our database only identi ed 521 HNC survivors who received treatment for lymphedema suggesting marked undertreatment of the disorder. The primary treatment modality for those referred was MLD (80%) with only a small percentage receiving compassion garments (13.6%) and even fewer (8.6%) receiving APCD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is just over half of the historically reported low range of 12% and a small fraction of the incidence of 90% reported in contemporary studies. [8][9][10][11][12] Our database only identi ed 521 HNC survivors who received treatment for lymphedema suggesting marked undertreatment of the disorder. The primary treatment modality for those referred was MLD (80%) with only a small percentage receiving compassion garments (13.6%) and even fewer (8.6%) receiving APCD.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The reported prevalence of lymphedema in HNC survivors ranges from 12% to more than 90%. [8][9][10][11][12] This variation is due to methodological differences between studies with contemporary studies favoring the high range of prevalence. 8,12 HNL is not simply a cosmetic issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 1 observational study identified in the present review used this tool. Another recent systematic review on HNCaL assessment highlighted 2 objective measures: (1) computed tomography for external and internal HNCaL and (2) ultrasonography for external lymphedema . In the present review, 1 RCT used ultrasonography, and none used computed tomography.…”
Section: Discussionmentioning
confidence: 86%
“…In the present review, 1 RCT used ultrasonography, and none used computed tomography. For monitoring internal lymphedema, the current criterion standard is endoscopy-based measures . This review identified 6 studies (2 RCTs, 4 observational studies) of adjunct therapies that used various endoscopic measures, with none showing clear improvement.…”
Section: Discussionmentioning
confidence: 99%